2016
DOI: 10.1080/1540496x.2016.1180284
|View full text |Cite
|
Sign up to set email alerts
|

If You’re Going Through Hell, Keep Going: Non-linear Effects of Financial Liberalization in Transition Economies

Abstract: Did increasing the level and pace of financial liberalization during transition expose countries to crises? And if a crisis did strike, did liberalization do more harm or good? Using a database of 28 transition economies over 22 years, this paper examines these questions across a host of economic outcomes, including savings and the size of the private sector. The results provide evidence that, while liberalization may initially increase the probability of a crisis, the prospect of a crisis drops dramatically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…In turn, financial liberalization could affect the risks of a crisis. This hypothesis has been tested in recent empirical studies, which found that liberalization tends to increase the probability of a crisis (Tornell, Westermann, and Martinez 2004;Rancière, Tornell, and Westermann 2006), although this risk may decline when the institutional environment is strong (Demirgüç-Kunt and Detragiache 1998) or as liberalization proceeds (Hartwell 2017).…”
Section: The Impact Of Liberalization On the Risk Of Crisismentioning
confidence: 99%
“…In turn, financial liberalization could affect the risks of a crisis. This hypothesis has been tested in recent empirical studies, which found that liberalization tends to increase the probability of a crisis (Tornell, Westermann, and Martinez 2004;Rancière, Tornell, and Westermann 2006), although this risk may decline when the institutional environment is strong (Demirgüç-Kunt and Detragiache 1998) or as liberalization proceeds (Hartwell 2017).…”
Section: The Impact Of Liberalization On the Risk Of Crisismentioning
confidence: 99%